Pengaruh Suasana Cafe dan Kualitas Pelayanan Terhadap Kepuasan Konsumen di H’old Coffee - Abdul Basit; Yasmin Nurul Haq Almuqayyim; Dea Julvani; Aura Ginta Setia; Dimas Linggarto; Ajrina Wina Maryam (TAFAQQUH, 2025)
The growth of the café industry as part of the service sector has increased significantly in line with changing consumer preferences for holistic experiences. In this context, physical atmosphere and service quality are two crucial elements that influence Customer satisfaction. This research seeks to examine the impact of the café atmosphere and service quality on customer satisfaction at H'old Coffee. A quantitative method was employed by distributing questionnaires to 54 respondents using an accidental sampling technique. The findings reveal that service quality significantly influences customer satisfaction, whereas the café atmosphere does not have a notable impact. Together, both factors account for 74.7% of the variation in customer satisfaction.. These findings confirm that improving service quality is a more effective strategy in creating customer satisfaction and loyalty. This research provides a practical contribution for cafe managers in formulating customer-oriented service policies to strengthen business competitiveness.